Anthocyanins in Colorectal Cancer Prevention Review - Ni Shi; Xiaoxin Chen; Tong Chen (Antioxidants, 2021)
Colorectal cancer (CRC) is still a big health burden worldwide. Nutrition and dietary factors are known to affect colorectal cancer development and prognosis. The protective roles of diets rich in fruits and vegetables have been previously reported to contain high levels of cancer-fighting phytochemicals. Anthocyanins are the most abundant flavonoid compounds that are responsible for the bright colors of most blue, purple, and red fruits and vegetables, and have been shown to contribute to the protective effects of fruits and vegetables against cancer and other chronic diseases. Berries and grapes are the most common anthocyanin-rich fruits with antitumor effects. The antitumor effects of anthocyanins are determined by their structures and bioavailability as well as how they are metabolized. In this review, we aimed to discuss the preventive as well as therapeutic potentials of anthocyanins in CRC. We summarized the antitumor effects of anthocyanins and the mechanisms of action. We also discussed the potential pharmaceutical application of anthocyanins in practice.